Effect of annealing time on electrical and mechanical properties of 0.7(Pb(Zr1/2Ti1/2)O3) - 0.3(Pb(Zn1/2Nb2/3)O3ceramics - G. Rujijanagul (2018)
The solid solution between the normal ferroelectric and relaxor ferroelectric of 0.7(Pb(Zr1/2Ti1/2)O3) - 0.3(Pb(Zn1/2Nb2/3)O3 was synthesized by the columbite method. After sintering, the ceramics were investigated as a function of annealing time. Properties of the ceramics were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), dielectric spectroscopy, and hardness tester. The results indicated that dielectric constant of the annealed samples was enhanced. In addition, hardness values of the annealed samples were also improved. Copyright © Taylor & Francis Group, LLC.